Pengaruh Pendinginan Awal terhadap Pertumbuhan Umbi Lapis Bawang Merah (Allium cepa L.) sebagai Dasar Pembuatan Brosur bagi Masyarakat - Rahmaniah, Ummu (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This study aims to determine the effect of pre-cooling on the growth of shallot (Allium cepa L.) bulbs as a basis for compiling brochures for the community and to develop research results on the growth of shallot (Allium cepa L.) bulbs. This type of research is pure experiment and development research. Data collection techniques in this study are using techniques: 1) observation; 2) validation; and 3) documentation. The data analysis technique used is Analysis of Variance (ANOVA) at a significance level of 5%. The treatment given to Bima local shallots was 1 treatment without refrigeration and 4 pre-cooling treatments, each of which was repeated 4 times to obtain 20 experimental units. The parameters measured are: 1) plant height; 2) number of leaves; and 3) leaf diameter. The results of this study indicate that, on the parameters of plant height, number of leaves, and leaf diameter it is stated that fcount <ftable indicates no difference at a significant level. From the results of development research in the form of brochures compiled and validated by content or material experts with an average score of 76.6%, validation of language experts with an average score of 74%, and display expert validation with an average score of 77.5%, as well as community readability test with an average score of 79.83%. Therefore, the brochure does not need to be revised and the contents of the brochure are legible.